2009
DOI: 10.1021/jm901214q
|View full text |Cite
|
Sign up to set email alerts
|

Indol-3-ylcycloalkyl Ketones: Effects of N1 Substituted Indole Side Chain Variations on CB2 Cannabinoid Receptor Activity

Abstract: Several 3-acylindoles with high affinity for the CB(2) cannabinoid receptor and selectivity over the CB(1) receptor have been prepared. A variety of 3-acyl substituents were investigated, and the tetramethylcyclopropyl group was found to lead to high affinity CB(2) agonists (5, 16). Substitution at the N1-indole position was then examined. A series of aminoalkylindoles was prepared and several substituted aminoethyl derivatives were active (23-27, 5) at the CB(2) receptor. A study of N1 nonaromatic side chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
108
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(116 citation statements)
references
References 46 publications
3
108
1
1
Order By: Relevance
“…These chemical shifts in 1 H and 13 C spectra of compound 16 are not characteristic for indole derivatives and differ substantially from the data for compounds 2 and 10 and from Refs. [20,26,27] data. We suggested that these could be rationalized by a mesomeric structure where positive charge is delocalized along a conjugation chain from indole N (resonance structure 16(N + )) to furan O (resonance structure 16(O + )) (Fig.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…These chemical shifts in 1 H and 13 C spectra of compound 16 are not characteristic for indole derivatives and differ substantially from the data for compounds 2 and 10 and from Refs. [20,26,27] data. We suggested that these could be rationalized by a mesomeric structure where positive charge is delocalized along a conjugation chain from indole N (resonance structure 16(N + )) to furan O (resonance structure 16(O + )) (Fig.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…Further search has revealed packets with plant mixes and a packet with a powder which was later identified as (1-pentyl-1H-indol-3-yl)(2,2,3,3-tetramethylcyclopropyl)methanone (2) (our symbolic notation 'TMCP-018'). According to [20,21] the compound acts as a selective full agonist of the cannabinoid receptors CB 2 and CB 1 . Later smoking mixes containing 'TMCP-018' became extremely widely spread in Russia with a maximum in February 2012: only in Ekaterinburg there were 2-5 seizures daily.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although UR-144 induces hypothermia and reduces locomotor activity in experimental animals (Wiley et al, 2013;Gatch and Forster, 2015;Banister et al, 2015), the effects are weaker than other typical synthetic cannabinoids such as JWH-018 and AM-2201 (Banister et al, 2015). It is possible that these phenomena are explained by receptor selectivity of UR-144, as its Ki values are 150 nM and 1.8 nM for CB 1 and CB 2 , respectively (Frost et al, 2010). On the other hand, UR-144 and its fluoro derivative XLR-11 [(1-(5-fluoropentyl)-1H-indol-3-yl)(2,2,3,3-tetramenthylcyclopropyl)methanone] contain a cyclopropyl ring (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…18,19 Additionally, the naphthalene group of JWH-018 is not mandatory for CB 1 binding, and many 1-alkylindoles containing alicyclic 3-acyl groups have been reported as cannabinoid ligands, including adamantane derivatives. 63 Indeed, analogues containing the N-(adamtan-1-yl)-1-alkyl-1H-indole-3-carboxamide core of SDB-001 are listed as prophetic structures in several patents by Makriyannis and colleagues, although SDB-001 itself is not described. 64−66 Pasquini and coworkers recently prepared several 5-arylated N-(adamtan-1-yl)-1-pentyl-1H-indole-3-carboxamides, however, these compounds generally functioned as selective CB 2 receptor inverse agonists rather than CB 1 receptor agonists.…”
mentioning
confidence: 99%